Effectiveness of Explicit Teaching Using Augmented Reality in Teaching Sensory Organs to Students with Autism Spectrum Disorder - KARAASLAN, ÖZCAN (My University, 2023)
In this study, it was aimed to determine the effectiveness of the explicit teaching method using ¨Augmented Reality (AR)¨ in teaching sensory organs to students with ̈Autism Spectrum Disorder (ASD) ̈. The participants of this research are consist of three male students with ASD. They are attending Special Education Vocational School. The design of this research is the multiple probe design with probe conditions across subjects. The dependent variable of the research is the learning level of the structure and functions of the sensory organs of the students with ASD. The independent variable is the explicit teaching method using AR. The findings indicated that the explicit teaching method using AR is effective in teaching the structure and functions of the sensory organs in three students with ASD. It was revealed that the participants maintained their acquisitions about sensory organs they learned in the 1st, 2nd and 3rd weeks. Additionally, generalization data indicated that three students with ASD generalized the skills they learned.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Özel Eğitim; Social Sciences and Humanities; Education; Special Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, ÖZEL; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SPECIAL; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities